COMORBIDITY IN CHRONIC GASTRODUODENITIS IN CHILDREN AND ASSESSMENT OF THE INFLUENCE OF INDIVIDUAL FACTORS ON ITS SEVERITY - Anfinogenova , Olga Borisovna; Shebalina, Anastasia Olegovna (Mother and Baby in Kuzbass, 2026)
The article highlights the issues of combined damage to the digestive system in children and adolescents with thyroid pathology. The high incidence of diseases of the upper digestive tract and the difficulties in their control make the study of their joint course (comorbidity) extremely relevant.Study objective – to determine the influence of the studied anamnestic factors on the severity of morphological manifestations in the upper digestive tract in children with combined thyroid pathology living in an ecologically and endemically unfavorable region (Kemerovo Region).Materials and methods. The study involved 105 patients aged 7 to 17 years with an endoscopically confirmed diagnosis of chronic gastroduodenitis and concomitant thyroid pathology.Results of the study. The diagnostic model predicted that there is a high degree of association of overweight and obesity with more pronounced morphological changes in the gastric and duodenal mucosa in children and adolescents with concomitant diffuse nontoxic goiter. The fact that diffuse nontoxic goiter is combined with grade I and II obesity demonstrated earlier periods, not typical for this age, of more pronounced forms of damage to the upper digestive tract in children from 7 years of age and older.Conclusions. The most significant features have been identified, the involvement of which in the implementation of more pronounced morphological forms of chronic gastroduodenitis has been proven by modern predictive statistical methods. In particular, the child's age, body mass index, and the presence of diffuse nontoxic goiter show a high association with a heavier form of chronic gastroduodenitis. The study of these parameters is of key importance for the management of patients with severe, often recurrent gastroenterological pathology.
Keywords: diffuse euthyroid goiter; children; chronic gastroduodenitis; comorbidity